Birds, dung beetles and trees in a fragmented landscape of Cañas, Guanacaste: relationships between tree cover and biodiversity - Sabido, Eugenio W. (Centro Agronómico Tropical de Investigación y Enseñanza (CATIE), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2001